Dampak Return On Asset (ROA), Return On Equity (ROE) Dan Net Profit Margin (NPM) Pada Harga Saham PT. Gudang Garam Tbk - Hasmirati; Akuba, Alfin (Jurnal Manajemen Bisnis, 2020)
This study predicts how much the impact of return on equity, return on assets, and net profit on the PT will be affected simultaneously or partly. Gudang Garam Tbk. Gudang Garam, the equity return component has a positive and negligible impact on the return on assets, and the return on assets component has a net and negligible impact on the yield. Margins have distorted and negligible effects on stock prices.